Super-Resolution Correlating Optical Endoscopy - Oskar Tamm; Vipin Tiwari; Shivasubramanian Gopinath; Aravind Simon John Francis Rajeswary; Scott Arockia Singh; Joseph Rosen; Vijayakumar Anand (IEEE Access)
Optical endoscopy is a widely used minimally invasive diagnostic tool for imaging internal organs. The imaging resolution is defined by the numerical aperture of the objective lens. In this study, we proposed and demonstrated a Super-resolution Correlating OPtical Endoscopy (SCOPE) system. In SCOPE, modified recording and reconstruction methods are introduced with the existing built-in endoscopy lens. Instead of recording a single image, multiple images of the object are recorded by scanning the tip of the endoscope around the object. The recorded low-resolution images of the object are arranged as sub-matrices in a 2D matrix. Another similar 2D matrix with either recorded or synthesized point spread functions (PSFs) is created. The 2D matrices of the object and the PSF were processed using a deconvolution algorithm to reconstruct a super-resolution image of the object. Both simulation and proof-of-concept experimental studies have been presented. SCOPE neither requires any additional optical element nor any changes in the endoscopy system itself; therefore, it can be easily implemented in commercial endoscopy systems.